2012
DOI: 10.1021/jp303316s
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald-Like Ripening of the Anomalous Mesoscopic Clusters in Protein Solutions

Abstract: Metastable clusters of mesoscopic dimensions composed of protein-rich liquid exist in protein solutions, both in the homogeneous region of the solution phase diagram and in the region supersaturated with respect to an ordered solid phase, such as crystals; in the latter region they are crucial nucleation sites for ordered solids. We monitor, using three optical techniques, the long-term evolution of the clusters in lysozyme solutions at conditions where no condensed phases, liquid or solid, are stable or prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
112
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(131 citation statements)
references
References 44 publications
18
112
1
Order By: Relevance
“…Secondly, it is striking that we find such a strong dependence of the nucleation kinetics--and the impact of filtration thereon--on protein stock solution age. This is reminiscent of two recent papers that have revealed that protein clusters undergo a gradual maturation, i.e., the mean cluster size grows over time (21,41). However, they report on processes operating on a timescale of hours and days, certainly not weeks and months, as is the case here.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Secondly, it is striking that we find such a strong dependence of the nucleation kinetics--and the impact of filtration thereon--on protein stock solution age. This is reminiscent of two recent papers that have revealed that protein clusters undergo a gradual maturation, i.e., the mean cluster size grows over time (21,41). However, they report on processes operating on a timescale of hours and days, certainly not weeks and months, as is the case here.…”
Section: Discussionsupporting
confidence: 69%
“…The dependence of protein stock solution age on the crystallization outcome is perhaps not entirely unexpected. Works in the past have reported cluster maturation (i.e., increase in size) through an Ostwald-like ripening process (21,41). We also observe that the reduction in nucleation rate becomes more pronounced at higher σ-values--the nucleation rate drops to a basal level after filtration which is independent of σ. σ was varied by increasing the bulk protein concentration, and thus by extension, the cluster number density in the mother liquor.…”
Section: Resultssupporting
confidence: 61%
“…the growth of larger clusters at the expense of smaller ones. Something like ripening has in fact been reported by Li et al [9] albeit with the unusual feature that the ripening stops while there is still a finite population of clusters. If the present model were correct, this "ripening" would have to be reinterpreted: perhaps as a slowly relaxing transient.…”
Section: Discussionsupporting
confidence: 59%
“…2,34 The combination of weaker binding and structural destabilization classifies R248Q among the strongest predictors of patient death in ovarian cancer. 35 We examine the existence of two distinct liquid phases: macroscopic liquid, similar to the phase found with other partially disordered proteins, [17][18][19][20][21] and mesoscopic protein-rich clusters observed with numerous globular proteins [23][24][25]36,37 and recently found for wild type p53. 38 We establish that p53 R248Q forms mesoscopic clusters, which are distinct form the macroscopic dense liquid, and that they host the nucleation of amyloid fibrils.…”
mentioning
confidence: 99%